Pengaruh Desain Pembelajaran Terhadap PAI Prestasi Belajar dan Karakter Siswa - Silva Vadila Putri; Silvi Vadila Putri; Gusmaneli Gusmaneli (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study discusses the impact of the design of Islamic Religious Education (PAI) learning on students' academic achievement and character development. An effective learning design plays an important role in enhancing students' understanding of religious material while simultaneously shaping character in line with Islamic values. Contextual and active learning, such as value-based projects and the use of technology, not only encourages student engagement but also develops critical thinking skills. This research uses a descriptive qualitative approach with a literature review, examining various sources to explore the relationship between PAI learning design, academic performance, and student character. The results show that a well-designed learning process can improve students' academic achievement in cognitive aspects and also contribute to strengthening their character through the instilling of Islamic values. Learning that involves direct experience and self-reflection enables students to apply these values in daily life. Therefore, an effective PAI learning design not only focuses on improving academic performance but also on the development of noble character, which prepares students to face life’s challenges with intelligence and good morals